Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
[tex]\displaystyle f[g(2)] = 3[/tex]
Step-by-step explanation:
We are given the two functions:
[tex]\displaystyle f(x) = -2x - 1\text{ and } g(x) = -x[/tex]
And we want to find the value of:
[tex]\displaystyle f[g(2)][/tex]
First, evaluate g(2):
[tex]\displaystyle \begin{aligned} g(2) &= -(2) \\ &= -2\end{aligned}[/tex]
Substitute:
[tex]\displaystyle f[g(2)] = f(-2)[/tex]
Evaluate f(-2):
[tex]\displaystyle \begin{aligned} f(-2) &= -2(-2) - 1 \\ &= 4 - 1 \\ &= 3\end{aligned}[/tex]
Therefore:
[tex]\displaystyle f[g(2)] = 3[/tex]
If you put 2x-1 and g(x), just put 437x-1(g(2) it would be marked correct
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.